ANALISIS TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MEMBACA DI PERPUSTAKAAN SEKOLAH PADA SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI PEKANBARU - Rawi Gunawan; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by problems that arise from observationsmade by researchers according to the reality that occurs in the field, indicating that thelack of attention to the condition of the library is often the cause of obstacles forstudents in enriching their knowledge through existing library materials as a means ofincreasing knowledge . The formulation of the problem in this study is